Clazomenian Sarcophagus from the British Museum: The Semantic Aspects of the Decoration and Shape - Nenakhova, Maria N. (Actual Problems of Theory and History of Art, 2021)
In Asia Minor, richly decorated terracotta sarcophagi of the 6th–5th centuries BC were found in the necropolises of several Ionian centers: Clazomenae, Old Smyrna, Miletus, etc. The problem of “decoding” the paintings on these funerary items has remained since the end of the 19th century. Today, two points of view on the problem coexist in art history. The first is that the paintings bear purely a decorative function and do not carry additional connotations (R.M. Cook and others), and the second is that the paintings are a kind of a “code” or “language” expressed in the images and their combinations to reflect the Clazomenian burial rites and religious beliefs (E. Kirchner and others).The article expands on the second point of view. It proposes to combine the semantic understanding of paintings with the analysis of the form using the example of the Clazomenian sarcophagus from the British Museum (510–480 BC). Not only the decoration but the sarcophagus as a whole brings together all the main subjects and meanings. The key symbolic images (various battles scenes, agones, mixomorphic creatures, ornamentation, etc.) have a certain location on the lid and chest — the covering, framing and enclosing structural elements. This can be explained by the internal logic of the sequence of “events”: from battles (and death) to funeral games and finally an arrival in Elysium. From the comprehensive reading of the form and the decoration, the basic idea of the sarcophagus-heroon is formulated, which in semantic terms is comparable to the Anatolian burial structures of the same period.
Keywords: Clazomenian terracotta sarcophagi; Archaic period; funeral cult; funeral rite; black-figure painting; heroon; agon; chariot races; hoplite battles